Developing a virtual adaptive sports program in response to the COVID-19 pandemic - Blauwet, C. A.; Robinson, D.; Riley, A.; MacEwan, K.; Patstone, M.; Dubon, M. E. (Practice Management, 2020)
In recent years, adaptive sports have become a mainstay of the rehabilitation process given their potential to enhance physical and mental health outcomes in people with disabilities. The rapid onset of the COVID-19 pandemic created numerous challenges to the management of traditional, in-person adaptive sports programs. This article provides a step-by-step guide on the design and implementation of a virtual adaptive sports program while also describing the challenges and benefits of such programs. Through a quality improvement initiative, we demonstrate similar participant reported outcomes in psychological health, physical health, and functional domains when comparing traditional adaptive sports to virtual programming.